Calcineurin activation and scaffolding in Aß‐induced synaptic dysfunction. (20th December 2022) - Prikhodko, Olga; Sanderson, Jennifer L; Freund, Ronald K; Sullivan, Emily; Kennedy, Matthew J; Dell'Acqua, Mark L
Abstract: Background: Calcineurin (CaN) is a protein phosphatase that is essential for synaptic long‐term depression (LTD) through its regulation of AMPA‐type glutamate receptors (AMPAR). AMPAR regulation by CaN is critically mediated by the postsynaptic scaffold protein A‐kinase anchoring protein 150 (AKAP150), which localizes a pool of CaN to the postsynaptic membrane. Our lab has generated knockin mice carrying a mutant version of AKAP150 lacking its CaN‐binding site, the PxIxIT motif; AKAP150ΔPIX (PIX). LTD does not occur in these mice, underscoring the importance of the synaptic pool of CaN for normal synaptic function and plasticity. Pharmacological inhibition of calcineurin prevents diverse manifestations of Aβ‐mediated synaptotoxicity, including long‐term potentiation (LTP) blockade, synapse loss, and impaired learning and memory in AD mouse models. However, the importance of synaptically‐localized calcineurin in Aβ synaptotoxicity is unknown. Method: To test our novel hypothesis that Aβ synaptotoxicity requires spatial positioning of CaN at the synapse via AKAP150 anchoring, we used our innovative AKAP150ΔPIX (PIX) knock‐in mouse model. Primary hippocampal neuronal cultures and acute hippocampal slices from WT and PIX mice were treated with various doses of Aβ oligomers and assayed for Aβ's effect on dendritic spine density, quantal calcium transients through NMDA receptors (both in culture), and LTP through extracellular field recordings (in slices). Additionally, utilizing the 5xFAD AD mouse model, we generated PIX/5xFAD mice to test long‐term behavioral (via radial arm water maze and contextual fear conditioning tasks) and electrophysiological effects (through field recordings) of the PIX mutation on the 5xFAD phenotype in 6‐month‐old animals. Result: The PIX mutation protects against acute Aβ‐mediated synaptic loss, decreased Ca 2+ entry through NMDA receptors, and LTP deficits. Long‐term, the PIX mutation rescues contextual fear conditioning memory, but not radial arm water maze performance or chronic LTP deficits of 5xFAD mice. Conclusion: Synaptically‐localized calcineurin is necessary for early Aβ‐mediated synaptic deficits. Long‐term Aβ exposure engages mechanisms beyond its AKAP‐anchored calcineurin pathway.